The regulation of “timeless” work in collective bargaining agreements - Paolo Tomassetti; Arianna Abbasciano (Labour & Law Issues, 2025)
This report provides an initial overview of the collective bargaining regulation of “timeless” work. This concept refers to work arrangements in which the duration or temporal allocation of job performance is eighter not predetermined or is left to the worker’s discretion. A cross-sectoral analysis was conducted on a range of national and company-level collective agreements, covering employment, para-subordination and self-employment. The report shows that, notwithstanding references to flexible arrangements, time continues to play a decisive role in both work organisation and remuneration, with few exceptions. These insights shed light on the role of collective autonomy in regulating “timeless” work, suggesting potential future developments of its protective framework.